2006
DOI: 10.1097/01.wnr.0000215771.61355.e1
|View full text |Cite
|
Sign up to set email alerts
|

Full-length tropomyosin-related kinase B expression in the brainstem in response to persistent inflammatory pain

Abstract: Supraspinal descending pathways from the periaqueductal gray and rostral ventromedial medulla dynamically modulate nociceptive transmission in the spinal dorsal horn. We examined the expression of the brain-derived neurotrophic factor receptor trkB in response to inflammation. No difference was observed in the number of neurons expressing trkB in the periaqueductal gray or rostral ventromedial medulla 3 h after inflammation; however, by 24 h, there was a significant increase in trkB expression in the periaqued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…BDNF exerts effects on nociception by binding to trkB.FL and initiating intracellular signaling cascades that lead to transcriptional changes. Noxious stimulation increases BDNF and trkB.FL production in the spinal dorsal horn [5][6][7][8][9] and brainstem [10,11], leading to hyperalgesia and the formation of nocifensive behaviors. Interfering with trkB.FL signaling via trkB.FL-specific exogenous antibody administration [12] or by blocking receptor activation in the chemicalgenetic transgenic trkB F616A mice [13] prevents the devel-opment of tissue-and nerve injury-induced thermal and mechanical hypersensitivity [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF exerts effects on nociception by binding to trkB.FL and initiating intracellular signaling cascades that lead to transcriptional changes. Noxious stimulation increases BDNF and trkB.FL production in the spinal dorsal horn [5][6][7][8][9] and brainstem [10,11], leading to hyperalgesia and the formation of nocifensive behaviors. Interfering with trkB.FL signaling via trkB.FL-specific exogenous antibody administration [12] or by blocking receptor activation in the chemicalgenetic transgenic trkB F616A mice [13] prevents the devel-opment of tissue-and nerve injury-induced thermal and mechanical hypersensitivity [14].…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were performed with the tester blind to the genotype of the mice and the treatment that they received. All mice tested were adult male mice (2-6 months of age weighing approximately 30 g. Details regarding the production of the inflammatory model using Complete Freund's adjuvant (CFA) can be found in Renn et al [ 11 ] and the antiretroviral model methods are detailed in Dorsey et al [ 37 ]. For capsaicin experiments, capsaicin (Sigma, St. Louis, MO) was dissolved in 100% dimethylsulfoxide (DMSO) followed by dilution with 0.9% saline to a concentration of 0.08 μg/μl.…”
Section: Methodsmentioning
confidence: 99%
“…The neurotrophin BDNF has been shown to be a potent modulator of pain processing in the CNS (Merighi, Salio, Ghirri, & al., 2008). Noxious stimulation increases BDNF production in the spinal dorsal horn (SDH)(Coull, et al, 2005) and brainstem (Renn, Lin, Thomas, & Dorsey, 2006), leading to hyperalgesia and the formation of mechanical allodynia. This is presumably because BDNF signaling participates in the development of windup and central sensitization in the SDH, using mechanisms similar to those in the development of long-term potentiation in the hippocampus (Latremoliere & Woolf, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by Mannion et al [ 72 ] showed that peripheral inflammation and C fiber electrical activity that increased BDNF expression in the DRG also increased full-length TrkB receptor levels in the dorsal horn (also see [ 85 , 101 ]). Even in the brainstem, TrkB levels are elevated in a model of chronic inflammatory pain [ 102 ].…”
Section: Bdnf Is An Important Modulator Of Neural Plasticitymentioning
confidence: 99%